Characterization of hydrocarbon reservoir by pore fluid and lithology using elastic parameters in an x field, Niger delta, Nigeria - ., Akpabio; O, Idara; ., Ojo; T, Odunayo (International Journal of Advanced Geosciences, 2018)
Quantitative rock physics analysis was carried out to determine the lithology and pore fluid of a reservoir in the Niger Delta. Density, compressional wave velocity and shear wave velocity logs were used as input to calculate elastic parameters such as velocity ratio, Poissonâ€™s ratio, and Bulk Modulus, after estimating the hydrocarbon reservoir in the X field. The calculated velocity ratio log was used to differentiate between sand, sandstone and shale. Poissonâ€™s ratio and velocity ratio were used delineate pore fluid content; gas sand, oil sand and sandstone formation from cross plot analysis. The reservoir in the field lies ranges from 9050 - 9426.5ft, (2760.25 â€“ 2874.93m), this confirm what is obtained in the Niger Delta Basin. The Net Pay zones show an economical viable reservoir, it Net pay depth is 39 â€“ 73.5ft. The Porosity and Permeability of the reservoirs suggested a productivity hydrocarbon reservoir. The reservoir lies between Gas sands, Oil sands and Brine sands, reservoir 2 and reservoir 3 are oil sand reservoirs while reservoir 1 lies between an oil sand and a brine sand.Â Â Â